EARNINGS FRAUD AND FINANCIAL STABILITY - Ahmad Abbas (Association of Certified Fraud Examiners Indonesia Chapter, 2017)
Earnings can be the goal for firms which desire to commit financial fraud. This study is propounded to show fraudulent earnings reporting and its relationship with the company’s financial stability. The samples used in this study are manufacturing firms listed on the Indonesian Stock Exchange during the period of 2010-2013. The data consisting of financial statements are processed using descriptive statistics, and the hypotheses are tested using logistic regression. The results of this study reveal that 22 financial statements are indicated earnings fraud. Of all the financial statements, 68 percent suffers from financial distress. This study shows that the firms with the improved financial stability tend to restrain themselves from committing earnings fraud. This study also finds that the firms which experience financial distress have a greater incentive to commit the fraud.